The Contribution of Innovation to Startups for Market Creation - Martins, Eros Augusto Asturiano (Revista de Negócios, 2020)
This article examined how the innovation in startups contributes to the creation of markets. The constructs â€œStrategies for the creation of marketsâ€ and â€œInnovationâ€ were covered in the theoretical framework. The scope of the research was startups and the specific objectives sought to analyze how innovation occurs and verifying the creation of the market through their innovation. The method of research was the qualitative exploratory, and data collection was performed by means of a structured script. Ten startup founders were interviewed and it was used the content analysis technique for data analysis. This article has shown that startups, even using an existing business model, innovate in the segment or the way they deliver their products, thus generating a value innovation and this is often caused by the ability to feel the pain of consumer. Some limitations were found in the research, such as the limited data on Brazilian startups, which already indicates a path for future research, as well as seeking to understand the functioning of the organizational structure of these companies, which still need to be better studied.